Motivation, Participation, and Perceptions of Semarang Runners Community Members Regarding Cardiovascular Fitness Levels - Syafii, Muhammad Luthfi (Journal of Physical Education and Sports, 2024)
This study aims to determine the influence of Motivation, Participation and Perception of Semarang Runners Community Members on Cardiovascular Fitness Levels. The research method used in this research is a mixed approach or often called mixed method. There are three research subjects used in this research, namely person, place, document. The sampling technique used was snowball sampling. Research results 1) The results of the F test of the influence of motivation on cardiovascular fitness show that (Regression 456,789, Residual 987,654, Total 1444,443): Total variability in the data, which is divided into variability explained by the model (Regression) and variability not explained by the model (Residual ), 2) Participation in a running community such as Semarang Runners can provide various benefits, both in terms of social, psychological and physical health, 3) Perception of the community and fitness also influences the quality of life of members. The conclusion of this research is that there is a significant influence of motivation on cardiovascular fitness, there is an influence of participation on cardiovascular fitness, and there is an influence of perception on cardiovascular fitness.